Classical Discourses of Liberation: Shared Botanical Metaphors in Sarvāstivāda Buddhism and the Yoga of Patañjali. (1st August 2018) - O'Brien-Kop, Karen
Abstract : Conventionally, the label 'classical yoga' has been aligned with-and sometimes conflated with-the text of Patañjali's Yogasūtra. Yet if we broaden the scope of inspection to a wider textual corpus, we can identify a richer and more complex discourse of classical yoga in soteriological contexts. This discourse is also employed in Buddhist Sarvāstivāda traditions and is semantically and metaphorically entangled across religious boundaries. By comparing passages from the Pātañjalayogaśāstra and the Abhidharmakośabhāṣya, this article highlights the botanical image of the seed and its seedbed (the substratum) as a key metaphorical structure in the soteriology of the two texts.